INFLUENCE OF VITAMIN E ON PANCREATIC ACINAR CELL MORPHOLOGY AND SERUM AMYLASE CONCENTRATIONS IN ALCOHOL-INDUCED PANCREATIC TOXICITY - Noman Ullah Wazir,; Farzana Salaman,; Shamaila Wadud,; Ambereen Humayun,; Asma Amir,; Momina Haq, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Misusing alcohol can cause damage to different tissues in the body, resulting in conditions like alcoholic liver disease, pancreatitis, cardiomyopathy, neurotoxicity, muscle wasting, weakened immune system, hormonal disruptions, birth defects, and bone loss. The objective of this research was to evaluate how alcohol affects the exocrine pancreas histology and the levels of amylase in the blood serum. Additionally, it aimed to explore whether vitamin E provides a safeguard against alcohol-induced harm to the pancreas in rabbits. Methods: A laboratory-based experimental investigation was carried out at Peshawar Medical College involving eighteen healthy adult male domestic rabbits weighing between one to one and a half kilograms each. The rabbits were divided into three groups. Group A, serving as the control, received normal saline as a placebo. Group B was administered a daily dose of 30 percent ethanol solution (30 ml/kg/day) in normal saline. Group C received a daily oral dose of 30% ethanol solution (30 ml/kg/day) in normal saline along with vitamin E (50mg/kg/day). Blood samples were collected for serum amylase analysis, while morphological assessment of acinar cells involved evaluating cell count, acinar size, acinar cell size, and acinar nucleus size. Results: Serum amylase levels did not exhibit a statistically significant variance between the control and experimental groups as p-value was >0.05. Furthermore, no notable distinctions were noted in the size and number of pancreas acini, cells of pancreatic acini, and pancreatic acinar cells nuclei between the control and experimental groups in both category E4 and Category E8, as p >0.05. Conclusion: There were no significant variations noted in the size and number of acini in pancreas, cells in pancreatic acini, and nuclei of cells in pancreatic acini. Consequently, the protective role of vitamin E against alcohol-induced pancreatic damage was not conclusively identified.